Transition‐Metal Dichalcogenides: Anisotropic Collective Charge Excitations in Quasimetallic 2D Transition‐Metal Dichalcogenides (Adv. Sci. 10/2020). Issue 10 (20th May 2020) - Tang, Chi Sin; Yin, Xinmao; Yang, Ming; Wu, Di; Wu, Jing; Wong, Lai Mun; Li, Changjian; Tong, Shi Wun; Chang, Yung‐Huang; Ouyang, Fangping; Feng, Yuan Ping; Wang, Shi Jie; et al.
Abstract : In article number 1902726, Xinmao Yin, Andrew T. S. Wee, and co‐workers observe 1D mid‐IR range anisotropic plasmons in quasi‐metallic WSe2 and MoS2 monolayers. In‐depth analysis reveals that the long‐range inter‐chain coupling is responsible for the 1D‐charge dynamics and the plasmon energy is dictated by the effects of spin–orbit coupling. Detailed investigation into these collective modes in 2D‐chained systems opens new opportunities for novel device applications and holds significant implications to the underlying mechanism that governs superconductivity in 2D‐transition‐metal dichalcogenide systems.